SUBSTITUSI TEPUNG KULIT SINGKONG RENDAH HCN PADA PEMBUATAN ROTI TAWAR - , LATIFAH NUR AINI, Prof. Dr. Ir. Sri Anggrahini, MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As number five the biggest producer of Cassava in the world, Indonesia produce big amount of cassava peel waste. The usage of cassava peel as white bread material will increase its economic value. The aim of this research are, (1) To know how much hydrogen cyanide can be reduced from cassava peel because of soaking. (2) To know the characteristic of white bread that made from cassava peel flour. (3) To determine the proportion of cassava peel flour to be substituted to wheat flour in bread which still acceptable for the panelist. There are three variation of soaking in this research, (1) control (without soaking), (2) soaking for 3 days, (3) soaking for 7 days. Substitution of the flour was conducted in 0%, 5%, 10%, 15%, 20%, and 25%. Physically properties including toughness, homogenity, degree of development also color and chemical properties proximate, salt and also its sensory properties were analyzed. It was found that soaking can reduce hydrogen cyanide content from 140,81 ppm (in sample without soaking), become 133,21 ppm (sample with 3 days soaking), and become 3,02 ppm (sample with 7 days soaking). After soaking, the content of ash, protein, fat, and water holding capacity were decreased. Whether moisture content and lightness of the flour were increased. It was used cassava peel flour with 7 days soaking for bread making.The characteristic of bread that made from cassava peel flour are: lower content of protein, higher content of ash, needs more water, lower degree of development, lower homogenity of pores, and its color were darker.